Correlation Between Marketing Strategies and Financial Performance of Micro Small Medium Enterprises in Isabela, Philippines (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Micro Small and Medium Enterprises (MSMEs) account for 99.56% of the economy. They employ 62.8% of the workforce, unfortunately they contribute only 35% of the Gross Value Added (GVA) and 25% of the Philippine export. They remain far less productive than large firms.  Notwithstanding the high rate of entry into the entrepreneurship activity, the failure rate is the highest in ASEAN leading to very low established business rate.This study aims to determine the financial performance of MSMEs, the level of implementation of marketing strategies and the relationship that exists between the financial performance and marketing strategies. The study uses the descriptive-correlational research method. There were 224 MSMEs involved in the study. These were selected from the different municipalities where MSMEs are prevalent. The survey questionnaire was utilized to record the interview from the respondents.It was found out that the financial performance of the MSMEs is "poor". with an overall score of 55. They are wanting in managing their receivables. they also have very low rate of return; they also have low survival rate because of their low rating on stability. In the context of marketing strategies, it was found out that MSMEs have very low rate of adoption of modern marketing strategies. They still employ the traditional way of enticing their customers. Lastly, it is found out that modern marketing strategies have significant and direct relationship with the MSMEs financial performance.